Differential risk of Alzheimer's disease in MCI subjects with elevated Abeta - Zhou, Bin; Fukushima, Masanori (Journal of the neurological sciences, 2024)
People with elevated beta amyloid have different risk and progress speed to Alzheimer's disease. The research is to validate the risk classification of AD developed in the Shanghai mild cognitive impairment (MCI) cohort study using ADNI data. The risk classification of AD in MCI was based on several optimal cut-off points of a novel parameter Cog_Vol. In total, 843 subjects with MCI were included, of whom 220 had elevated PET beta amyloid. 273 (32.3 %) and 70 (31.8 %) progressed to AD in all subjects and in those with elevated PET beta amyloid, respectively. The risk of AD in subjects whose Cog_Vol >340 was very low, while the risk for those with Cog_Vol less than 101 indicated a super high within 4 years of follow-up. Risk classification using Cog_Vol at an optimal value was able to detect subjects among those with PET-amyloid-elevated MCI were at greater risk of developing AD and were unlikely to develop AD within 4 years of follow-up. •Using hippocampus volume and cognition test ADAScog13 we created one new parameter Cog_Vol.•The parameter Cog_Vol can detect super high risk group (conversion rate >90%) and low risk group of AD in subjects with Aβ+ MCI•The method simple and practicable in identifying subjects when considering prevention clinical trial design of AD.